Studi Numeris Perbaikan Stabilitas Lereng Menggunakan Geotekstil pada Lumbung Air di Kabupaten Gresik - Malik, Dary; Chrismaningwang, Galuh; Setiawan, Bambang; Trimariat, Fathoro (Universitas Veteran Bangun Nusantara, 2024)
A slope is a land surface that has a slope towards the horizontal from a high point to a low point. Slope construction can occur naturally due to landslides or human intervention. Slope stability is the ability of a slope to maintain its shape to balance and not movement. Stability in water reservoirs is influenced by changes in the water table elevation of the reservoir which results in changes in soil moisture content and soil pressure. One of the methods of slope reinforcement is with geotextiles which have tensile strength properties and the ability to improve slope stability. Slope stability analysis can be conducted by numerical study using GeoStudio Program with 5 different methods. The results showed that the slope stability of the existing condition without reinforcement under the influence of water elevation and seismic load was obtained SF < 1,25 and classified as an unsafe slope. After planning the reinforcement of Hibritex LP75/75 geotextile on the slope with the same influence, the safety factor value is more than 1,25 and is classified as a safe slope.